Internalisasi Nilai-nilai Keislaman dan Kebangsaan pada Perguruan Tinggi Keagamaan Islam Negeri - Bukhari, Ahmad (LP2M IAIN Samarinda, 2019)
Today, the Islamic campus is being hit by complex problems. The complicated problem is the threat of radicalism and terrorism in the name of religion (Islam), whether carried out by individuals or groups and networks affiliated with certain radical organizations such as ISIS, JI, JAT, and NII. Not only Islamic revival movements but also the tarbawi propaganda movement (PKS), Tahriri (HTI), and Salafi (Wahabi) also pose a serious threat to the integrity of the nation and state. For this reason, it is necessary to internalize Islamic values and nationality as Islam rahmatanlilaminalamin. The purpose of this research is to know and understand the internalization of Islamic values and nationalities in IAIN Samarinda, UIN Maulana Malik Ibrahim Malang, and UIN Sunan Kalijaga Yogyakarta. This research is a qualitative research with the type of educational research that is the development of Islamic educational thought. This research is a field research and the data sources in this study are primary data sources in the field, specifically: the actors of Islamic universities, chancellors, lecturers, and students. In this study, the methods used in collecting data were observation, interviews, focus group discussions, and documentation. The results of the study in preventing and counteracting various forms of religious radicalization in PTKI with strategic steps: (1) strengthening Islamic insights and nationality through the campus boarding program; (2) deradicalization through strengthening student organizations; (3) selective in accepting students and lecturers; (4) providing moderate, inclusive and humanist Islamic literature, and (5) establish the millennial peace ambassadors on social media.